Voices - Le Guin, Ursula K., 1929- (London : Orion Books, 2007)
Young Memer takes on a pivotal role in freeing her war-torn homeland from its oppressive captors.
Young Adult.
Young Adult
Keywords: Good and evil -- Juvenile fiction; Coming of age -- Fiction; Fantasy; Good and evil -- Fiction; Bildungsromans; Good and evil -- Fiction; Fantastic fiction; Fantastic fiction